2020
DOI: 10.1039/d0cp02792h
|View full text |Cite
|
Sign up to set email alerts
|

Ternary multicomponent Ba/Mg/Si compounds with inherent bonding hierarchy and rattling Ba atoms toward low lattice thermal conductivity

Abstract: Compositional tailoring externally enables fine-tuning of thermal transport parameters of materials by dual modulation of electronic or thermal transport properties. We theoretically investigate the lattice dynamics of three particularly ternary...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Thus, the group velocity of acoustic phonons plays an important role in determining the lattice thermal conductivity. 49,50 As shown in Fig. 5(a) and (b), the group velocities of three acoustic branches are far higher than those of the optical modes, which is in agreement with the dispersed relation of the phonon band.…”
Section: Resultssupporting
confidence: 83%
“…Thus, the group velocity of acoustic phonons plays an important role in determining the lattice thermal conductivity. 49,50 As shown in Fig. 5(a) and (b), the group velocities of three acoustic branches are far higher than those of the optical modes, which is in agreement with the dispersed relation of the phonon band.…”
Section: Resultssupporting
confidence: 83%
“…Figure b shows the lifetime of CaMgSi obtaining a value of 16.8 ps at acoustic branches. Li et al reported similar values of the Grüneisen parameter and lifetime for BaMgSi, Ba 2 Mg 3 Si 4 , and BaMg 2 Si 2 , identifying that they can be designed as low-thermal-conductivity materials …”
Section: Resultsmentioning
confidence: 95%
“…Li et al reported similar values of the Grüneisen parameter and lifetime for BaMgSi, Ba 2 Mg 3 Si 4 , and BaMg 2 Si 2 , identifying that they can be designed as low-thermal-conductivity materials. 32 …”
Section: Resultsmentioning
confidence: 99%
“…To estimate the bond interaction strength of selenium, we normalize the trace of interatomic force constant (IFC) tensor versus atomic distance , and show it in Figure . It can be seen that the nearest neighbors, separated by about 2.4 Å, have the largest interaction and are much stronger than the rest coordinated neighbor Se atoms, which is in sharp contrast to the resonant bonding feature of rocksalt IV–VI lead chalcogenides and ternary BaMgSi compounds. , From the above phenomenon we can infer that heat is easily confined in the quasi-1D (0D) Se atom chains (rings) when the system is vibrated, which leads to different heat transport mechanisms for t-Se and r-Se: the atom chain of t-Se acts like a heat transmission channel , while the Se6 ring in r-Se behaves like a heat transport fence to impede thermal transport, which induce obvious phonon–phonon scattering and consequently the reduced lattice thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the bond interaction strength of selenium, we normalize the trace of interatomic force constant (IFC) tensor versus atomic distance 68,69 and show it in Figure 7. It can be seen that the nearest neighbors, separated by about 2.4 Å, have the largest interaction and are much stronger than the rest coordinated neighbor Se atoms, which is in sharp contrast to the resonant bonding feature of rocksalt IV−VI lead chalcogenides and ternary BaMgSi compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%